Preparation and properties of polydimethylsiloxane-modified chitosan - Metha Rutnakornpituk (2018)
Preparation and properties of polydimethylsiloxane (PDMS)-modified chitosan are discussed herein. A series of PDMS with systematically varied molecular weights were first prepared via acid-catalyzed ring opening polymerization of octamethylcyclotetrasiloxane (D4) to obtain PDMS prepolymers. They were subsequently functionalized with allyl glycidyl ether to obtain epoxy functional groups at PDMS terminals. Their chemical structures and molecular weights were characterized using1H NMR,13C NMR and FTIR, and thermal properties were determined by DSC. The reaction of the epoxidized PDMS and chitosan was carried out in an acidic aqueous solution. Increasing the molecular weights of PDMS and/or its concentrations improved flexibility and water swellability due to the formation of PDMS microphase. Water contact angle and water vapor permeability measurements indicated that incorporation of the PDMS enhanced its hydrophobicity as compared to the unmodified one. © 2005 Elsevier Ltd. All rights reserved.